Strategi Pengembangan Kompetensi SDM Berbasis Digital untuk Meningkatkan Daya Saing UMKM di Era Transformasi Industri 4.0: Studi Kasus di Kabupaten Purworejo - Galuh Aditya (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
The purpose of this research is to identify the problems and human resource needs of MSMEs in Purworejo Regency. In addition, to enhance the competitiveness of SMEs in the 4.0 industrial era, a digital competency development strategy will also be created. The research method used is qualitative with a case study approach involving MSME actors, trainers, and stakeholders. The research results show that limited digital literacy and access to technology are the main obstacles. On the other hand, intensive technical training and mentoring have proven to enhance human resource capabilities, and development strategies that combine direct training, mentoring, and cross-sector collaboration are capable of increasing the competitiveness of SMEs through market expansion and operational efficiency. To support the digital transformation of SMEs, this research suggests the development of sustainable digital training programs that can be tailored to local needs.